2022
DOI: 10.1155/2022/9578307
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect and Related Mechanism of Action of Astragalus Compatible with Curcumin against Colon Cancer Metastasis in Mice

Abstract: Colon cancer (CC) is the third most common tumor worldwide. Colon carcinogenesis is strongly linked to inflammation. The initiation and progression of colon cancer may be influenced by epigenetic processes. Cancer metastasis is a multistep process involving several genes and their products. During tumor metastasis, cancer cells first enhance their proliferative capacity by lowering autophagy and apoptosis, and then, their capacity is stimulated by boosting tumors’ ability to take nutrients from the outside via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%